2014
DOI: 10.4103/0019-557x.132288
|View full text |Cite
|
Sign up to set email alerts
|

Does seasonal migration for sugarcane harvesting influence routine immunization coverage? A cross-sectional study from rural Maharashtra

Abstract: A cross-sectional study was conducted to estimate and to compare immunization coverage and to understand reasons of partial/non-immunization among children of seasonal migrant sugarcane harvesting laborers and nonmigrating children. Caretakers of a total of 420 children between 12 and 23 months age were interviewed in 30 clusters consisting 14 children from each cluster (seven from each group) by expanded program on immunization cluster survey method. Statistical analysis was performed with proportions, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Similarly, children of seasonal or short-duration migrants become vulnerable to nutrition insecurity as they lack easy access to subsidized food and fair worse than non-migrants on most health indicators [8]. Several studies have also documented that the uptake of immunization is low among migrants [9] because of lack of awareness, time constraints, high costs incurred for vaccination and difficulty in traveling to health centres in urban areas [1013]. As children stay unattended at their parents worksites, exposed to unhygienic living conditions and unsafe environment there are large concerns about their safety, and overall health and wellbeing [4, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, children of seasonal or short-duration migrants become vulnerable to nutrition insecurity as they lack easy access to subsidized food and fair worse than non-migrants on most health indicators [8]. Several studies have also documented that the uptake of immunization is low among migrants [9] because of lack of awareness, time constraints, high costs incurred for vaccination and difficulty in traveling to health centres in urban areas [1013]. As children stay unattended at their parents worksites, exposed to unhygienic living conditions and unsafe environment there are large concerns about their safety, and overall health and wellbeing [4, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of antenatal care (ANC) services was remarkably low among the migrants compared to the local population or long‐term migrants. This finding was reported among the migrant women that were either sampled from the slums, or from construction sites, or the seasonal migrants during sugarcane harvesting season . Kusuma et al reported that for ANC, migrants in Delhi mainly relied on government health facility (72%), but adequate ANC was accessed by only 20% of the migrant women .…”
Section: Resultsmentioning
confidence: 91%
“…The immunization rates are not satisfactory with a very low percentage of migrants' children completely immunized up to age. A greater proportion of children were either partially immunized or did not even receive a single vaccine; when full immunization by 1 year of age is considered, none of the children was fully immunized . The proportion of children who did not receive a single vaccine is notable among tribal migrants in Bhubaneswar City—40% and 25%, and among seasonal migrants in Beed, Maharashtra—23% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children of the labourers are either partially immunized or non-immunized because of the place or time of vaccination not known, unavailability of immunization services at site, inconvenient time of sessions, unaware of need for vaccination etc. (Pakhare, Pawar, Lokhande, Datta, 2014). The quality of life of sugarcane harvesting migrants deteriorates sharply at destination from the nominal quality of life at their source.…”
Section: Literature Reviewmentioning
confidence: 99%